RECURRENT OBSTRUCTIVE BRONCHITIS IN EARLY CHILDHOOD: RISK FACTORS AND PROGNOSIS - Shamsiddinova Dilorom Kamariddinovna,; Tursunqulova Zilola, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Over the last ten years, the incidence of the pathology of the bronchus-pulmonary system in children has increased 3.6 times, mainly due to acute and recurrent inflammatory diseases of the upper and lower respiratory tract. Thus, the problem of identifying children with recurrent episodes of acute obstructive bronchitis and an increased risk of developing asthma is relevant and promising. Defined as three or more episodes of bronchial obstruction within a twelve-month period, ROB occupies a central position in the spectrum of lower respiratory tract disorders in early childhood and serves as a recognised precursor to bronchial asthma in a substantial proportion of affected individuals. The global burden of this condition is considerable: epidemiological data indicate that obstructive bronchitis accounts for up to 30-40% of all acute respiratory illnesses requiring hospitalisation in children below five years of age, with prevalence figures varying markedly across geographic regions and socioeconomic settings. The increasing recognition of ROB as a distinct clinical entity, rather than merely a symptomatic manifestation of viral respiratory infection, has prompted intensified investigation into its pathophysiological underpinnings, modifiable risk determinants, and long-term respiratory outcomes.